ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN PADA PERUSAHAAN PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BEI PERIODE 2016-2018 - Mariya Ulfah; Penta Widyartati (JURNAL STIE SEMARANG, 2020)
Timeliness of financial statements has been regulated by the government in accordance with regulations issued by the Otoritas Jasa Keuangan (OJK) which states that public companies are required to submit financial reports no later than the fourth month after the financial year ends. But some companies that are not timely in presenting their financial statements. This study aims to find empirical evidence about the influence of company size, liquidity, profitability, leverage, auditor's opinion, and KAP's reputation on the timeliness of financial statement submission. The population in this study are property and real estate sub-sector services companies listed on the Indonesia Stock Exchange (Bursa Efek Indonesia (BEI)) for the period of 2016-2018, as many as 47 companies. The sample in this study were 35 companies taken by purposive sampling method. The dependent variable is, the timeliness of financial statement submission. While the independent variables in this study are company size, liquidity, profitability, leverage, auditor's opinion, and KAP's reputation. Data collection methods using the method of library research and documentation methods. Hypothesis testing uses logistic regression at a significance level of 5 percent. The results of hypothesis testing indicate that firm size variables significantly influence the timeliness of financial statement submission with a significance value of 0.024 <0.05. Liquidity variable does not affect the timeliness of financial statement submission with a significance value of 0.437> 0.05. The profitability variable does not affect the timeliness of financial statement submission with a significance value of 0.753> 0.05. The leverage variable does not affect the timeliness of the delivery of financial statements with a significance value of 0.512> 0.05. The auditor's opinion variable has a significant effect on the timeliness of the delivery of the financial statements with a significance value of 0.025 <0.05. KAP reputation variable does not affect the timeliness of financial statement submission with a significance value of 0.998> 0.05.